2018
DOI: 10.15761/gvi.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensivity Reactions to Steroids: Review

Abstract: The history of corticosteroids begins in the year of 1855 when Thomas Addison describes a "state of generalized languor, failure in the function of the heart, irritability in the stomach and changes of coloration in the skin", initially called melanodermia and later called Addison's disease, characterized by the lack of a substance produced in the adrenal glands [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…5). In vitro diagnostic tests, such as lymphocyte transformation or interferon-gamma (IFN-γ) assays, are not validated and are not available for clinical practice [9]. Skin prick tests (always negative) are useless for the diagnosis of delayed hypersensitivity to corticosteroids [38].…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…5). In vitro diagnostic tests, such as lymphocyte transformation or interferon-gamma (IFN-γ) assays, are not validated and are not available for clinical practice [9]. Skin prick tests (always negative) are useless for the diagnosis of delayed hypersensitivity to corticosteroids [38].…”
Section: Original Articlementioning
confidence: 99%
“…Because of the wide usage of corticosteroids, even uncommon allergic hypersensitivity reactions are clinically important, thus physicians (general practitioners as well as allergy and dermatology specialists) should be aware of such reactions. The allergic hypersensitivity reactions can be immediate (usually up to 1 hour after corticosteroid administration) or delayed (appearing after more than 1 hour up to several days after corticosteroid administration) [8][9][10][11][12]. Klim Gittelman et al and Borja et al reported immediate hypersensitivity reactions in 0.1-0.3% of patients under systemic corticosteroid treatment [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation